2010
DOI: 10.1038/jhg.2010.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth hormone 1 genetic polymorphism and susceptibility to colorectal cancer

Abstract: The aim of this study was to evaluate the relationship between smoking, alcohol drinking and genetic polymorphism of the growth hormone 1 gene (GH1) T1663A with reference to colorectal cancer. We conducted a case-control study with 315 cases of colorectal cancer and 438 population-based controls in the Jiangsu Province, China. GH1 T1663A genotypes were identified using PCR-RFLP (restriction fragment length polymorphism) methods. Information on smoking and drinking was collected using a questionnaire. Odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our results with GH1 are supported by two previous reports 14 15. Le Marchand et al initally suggested a reduction in risk of colorectal cancer with the homozygous variant genotype 14, and results from Gao and colleagues also report a reduced risk of colorectal cancer associated with this same GH1 genetic variant 15.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results with GH1 are supported by two previous reports 14 15. Le Marchand et al initally suggested a reduction in risk of colorectal cancer with the homozygous variant genotype 14, and results from Gao and colleagues also report a reduced risk of colorectal cancer associated with this same GH1 genetic variant 15.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is reasonable to consider that polymorphisms which may affect these hormonal concentrations could also be associated with precursor lesions. Two studies study has demonstrated that a genetic polymorphism in GH1 is associated with a decreased colorectal cancer risk 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is an important environmental risk factor in human cancers, but in previous study (Gao et al, 2010), we found no relationship between cigarette smoking and colorectal cancer risk. In the present study, we also found no interaction between smoking and XRCC1 polymorphisms on the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 70%
“…The background characteristics of cases and controls have been described in previous articles (Cao et al, 2008;Gao et al, 2010). The proportional distribution of females in controls was higher than that in colorectal cases.…”
Section: Resultsmentioning
confidence: 93%
“…The background characteristics of cases and controls have been described previously (Gao et al, 2010). The proportional distribution of females in controls was significantly higher than that in colorectal cases.…”
Section: Resultsmentioning
confidence: 88%